Application of Proportional Integral Derivative system as speed control on Mobile Robot Line Follower: submission of Journal Thesis - Raka Pramudiya Ramadani; Arie Qur'ania; Agus Ismangil (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
The development of the world of robotics in Indonesia is experiencing very rapid development compared to a few years ago, the use of PID Control-based technology is growing in the field of robotics. This line follower robot uses IR Line follower sensor to detect the black line and PID control to regulate the movement of the robot automatically, so that the robot can follow the line that has been made with direction. The Arduino Uno microcontroller in this robot design is the main part of the input and output control system. In this robot design, Arduino Uno is used as a microcontroller to control sensors that function as sensing / detection tools for robots. The working system of this robot is: how to run it by activating the power button on the back of the robot. The number of sensors and the accuracy of the PID control value can affect the comparison of the robot's travel time value from the starting point to the end of the test with two paths that have been tested, the results obtained 4 IR LF Sensors with an average travel time of 6.7 seconds on the first path and 13.5 seconds on the second path, better than 2 or 3 IR LF Sensors which have a difference of 0.64 seconds on the first path and 0.7 seconds on the second path. The above values can change according to the influence of component specifications, circumstances and robot environment during testing.